2005
DOI: 10.1002/lt.20518
|View full text |Cite
|
Sign up to set email alerts
|

Activation pattern of mitogen-activated protein kinases in early phase of different size liver isografts in rats

Abstract: Mitogen-activated protein kinases (MAPK) play a pivotal role in ischemia reperfusion injuries of heart and liver, but the activation pattern of MAPKs in the early phase of different size liver isografts remains unclear. The experiment is designed to investigate the activation pattern and role of MAPKs in isografts of the rat with different size liver transplantation. The animal models of different size graft liver transplantation (whole graft, 50% size, or 30% size, respectively) were established and the sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Our present study demonstrated that p42/p44 ERKs were significantly up-regulated in small-for-size liver grafts, accompanied by increased cell cycle progression and enhanced proliferative response. This finding further supports the notion that ERK signals may play an important role in I/R and small-for-size graft injury and liver regeneration as well [39,40]. However, the mechanism by which MAPK regulates gene expression and subsequently improves liver regeneration remains unclear and needs further investigation.…”
Section: Discussionsupporting
confidence: 80%
“…Our present study demonstrated that p42/p44 ERKs were significantly up-regulated in small-for-size liver grafts, accompanied by increased cell cycle progression and enhanced proliferative response. This finding further supports the notion that ERK signals may play an important role in I/R and small-for-size graft injury and liver regeneration as well [39,40]. However, the mechanism by which MAPK regulates gene expression and subsequently improves liver regeneration remains unclear and needs further investigation.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, APC treatment remarkably decreased TNF‐α and IL‐6 hepatic expression at 6 hours but not 24 hours after partial OLT. With a small‐for‐size graft model, their hepatic protein expression rapidly increased after OLT, peaked at about 6 hours, and then decreased slightly 41, 42. Additionally, APC is rapidly cleared within a few hours after its in vivo administration 43.…”
Section: Discussionmentioning
confidence: 99%
“…The protein was extracted from freshly frozen tissue specimens and subjected to WB analysis as described (Liang et al 2005). BrieXy, the protein concentrations were determined with bovine serum albumin (BSA) as the reference standard using Bio-Rad DC protein assay kit (500-0116, Bio-Rad, Richmond, CA).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%